Activation status of mucosal-associated invariant T cells reflects disease activity and pathology of systemic lupus erythematosus - Chiba, Asako (Arthritis Res Ther, 2017)
BACKGROUND: Mucosal-associated invariant T (MAIT) cells are innate-like lymphocytes constituting a large proportion of peripheral blood T cells expressing αβ T-cell receptor in humans. In this study, we aimed to investigate their involvement in systemic lupus erythematosus (SLE). METHODS: Peripheral blood MAIT cells from patients with SLE were assessed for their frequency, activation markers, and cell death by flow cytometry. The correlation between plasma cytokine levels and CD69 expression on MAIT cells was analyzed. The major histocompatibility complex class I-related protein MR1-restricted antigen-presenting capacity of antigen-presenting cells was investigated. Cytokine-mediated activation of MAIT cells in the absence of exogenous antigens was also examined. RESULTS: The frequency of MAIT cells was markedly reduced in SLE. The reduced number of MAIT cells was not attributable to the downregulation of surface markers, but it was partially due to the enhanced cell death of MAIT cells, possibly by activation-induced cell death. The CD69 expression levels on MAIT cells in SLE correlated with disease activity. Moreover, monocytes from patients with SLE exhibited increased ability to induce MAIT cell activation. The plasma concentration of interleukin (IL)-6, IL-18, and interferon (IFN)-α positively correlated with the expression levels of CD69 on MAIT cells in SLE. MAIT cells were activated by cytokines, including IFN-α, IL-15, and IL-12 plus IL-18, in the absence of exogenous antigens. CONCLUSIONS: These results suggest that MAIT cells reflect the pathological condition of SLE and that their activated status correlates with presence of disease.